Multibeam bathymetry raw data (Atlas Hydrosweep DS 3 echo sounder entire dataset) of RV Sarmiento de Gamboa during cruise iMirabilis2_Leg1 - Veerle A I Huvenne; Covadonga Orejas; Rodríguez, Pablo; Catherine Wardell (PANGAEA, 2024)
Raw multibeam and sound velocity data collected around Cabo Verde on the iMirabilis2 Cruise, 04/08/2021-26/08/2021, as part of the iAtlantic Project. The data were collected using an Atlas Hydrosweep DS-3 Multibeam Echosounder, using Atlas Naviscan and PDS2000 from Teledyne. The sound velocity profiles (SVP) were collected using CTD casts and XBTs. The dataset spans ~200m - 4500m water depth.